Economic Value of Florida Water Resources: Valuing the Quality of Water for Household Needs - Tatiana Borisova; Syed Irfan Ali Shah; Tara Wade; Xiang Bi; Kelly Grogan (EDIS)
Florida water-resource professionals deciding whether to implement a costly water protection program or to invest in better tap water treatment technology may wonder: Are such investments justified? What are the benefits of the program or investment decision? Just how highly do Floridians value their water? This 5-page fact sheet written by Tatiana Borisova, Syed Irfan Ali Shah, Tara Wade, Xiang Bi, and Kelly Grogan and published by the UF/IFAS Food and Resource Economics Department reviews studies that help assess the value Floridians assign to maintaining or improving the quality of the water supply. http://edis.ifas.ufl.edu/fe1059